ROLE OF IL-5 AND EOTAXIN IN DEVELOPMENT OF BLOOD EOSINOPHILIC REACTION DURING PULMONARY TUBERCULOSIS - U. V. Kolobovnikova (SPb RAACI, 2014)
Abstract. The  study  considers  some  aspects  of  pathogenetic  mechanisms  underlying  blood  eosinophilic  reactions  developing  in  pulmonary  tuberculosis,  taking  into  account  some  novel  data  obtained  by  means  of  modern  immunological  techniques.  It  was  revealed  that  IL-5  is  among  key  factors  determining  eosinophilic  reactions  of  blood  following  infection  with  M.  tuberculosis.  Blood  serum  IL-5  concentrations  proved  to  be  significantly  higher  in  patients  with  tuberculosis  accompanied  by  eosinophilia.  In  these  cases,  eotaxin  is  a  chemokine,  which  selectively  acts  upon  eosinophilic  cells.  Its  effects  include  prolonged  persistence  of  eosinophils  in  bloodstream,  along  with  initiation  of  eosinophil  adherence  to  vascular  endothelium,  thus  enabling  subsequent  migration  of  eosinophilic  leukocytes  to  the  foci  of  specific  granulomatous  inflammation.  (Med.  Immunol.,  2011,  vol.  13,  N  2-3,  pp  273-278)